Whole Genome Transcriptomic Analysis of Ovary Granulosa Cells Revealed an Anti-Apoptosis Regulatory Gene DLGAP5 in Polycystic Ovary Syndrome - Deng, Yan; Li, Hu; Song, Yi; Cen, Juan; Zhang, Yuying; Sui, Yi; Cui, Dexuan; Li, Tin Chiu; Xu, Yan; Wang, Chi Chiu; Chung, Pui Wah Jacqueline; Tang, Tao (Frontiers in Endocrinology, 2022)
The mechanisms underlining pathogenesis of polycystic ovary syndrome (PCOS) remain largely unknown. Dysfunction of ovarian granulosa cells plays an important role. The present study performed the lncRNA and mRNA profiling by whole genome transcriptomic sequencing of ovary granulosa cells from women with PCOS and investigated the potential role of differentially expressed gens (DEGs) in the pathomechanism of PCOS. In total, 1,936 DEGs (30 upregulated and 1,906 downregulated mRNAs and lncRNAs) were identified in the ovary granulosa cells between control and PCOS group. Functional enrichment analysis showed that DEGs were mainly associated with cytokine–cytokine receptor interaction, neuroactive ligand–receptor interaction, and olfactory transduction. qRT-PCR validated the upregulation of DLGAP5 mRNA in ovary from PCOS group when compared to control group. Immunostaining and TUNEL assays showed that DLGAP5 protein level was increased while apoptosis was decreased in follicles of ovary in PCOS group. In vitro functional assays showed that DLGPA5 knockdown repressed viability and proliferation, but enhanced apoptosis and disrupted cell cycle in granulosa cells; while DLGAP5 overexpression had the opposite effects in granulosa cells. In conclusion, the study showed differentially expressed lncRNA and mRNA profile in the granulosa cells in ovaries of PCOS. Functional results demonstrated that DLGAP5 is a dysregulated candidate gene in the pathogenesis of PCOS, especially granulosa cell apoptosis and proliferation.